MYC regulation of Glutamine-Proline regulatory axis is key in Luminal B breast cancer - Craze, Madeleine L.; Cheung, Hayley; Jewa, Natasha; Coimbra, Nuno D.M.; Soria, Daniele; El-Ansari, Rokaya; Aleskandarany, Mohammed A.; Cheng, Kiu Wai; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ellis, Ian O.; Rakha, Emad; et al. (Cancer Research UK, 2017)
Background: Altered cellular metabolism is a hallmark of cancer and some are reliant on Glutamine for sustained proliferation and survival. We hypothesise that the Glutamine-Proline regulatory axis has a key role in Breast cancer (BC) in the highly proliferative classes. Methods: Glutaminase (GLS), pyrroline-5-carboxylate synthetase (ALDH18A1) and pyrroline-5-carboxylate reductase 1 (PYCR1) were assessed at DNA/mRNA/protein levels in large well-characterised cohorts. Results: Gain of PYCR1 copy number and high PYCR1 mRNA was associated with luminal B tumours. High ALDH18A1 and high GLS protein expression was observed in the ER+/HER2- high proliferation class (Luminal B) compared with ER+/HER2- low proliferation class (Luminal A) (p=0.030 and p=0.022 respectively), however this was not observed with mRNA. Cluster analysis of the Glutamine-Proline regulatory axis genes revealed significant associations with molecular subtypes of breast cancer and patient outcome independent of standard clinicopathological parameters (p=0.012). High protein expression of the Glutamine-Proline enzymes were all associated with high MYC protein in Luminal B tumours only (p<0.001). Conclusion: We provide comprehensive clinical data indicating that the Glutamine-Proline regulatory axis plays an important role in the aggressive subclass of luminal BC and is therefore a potential therapeutic target.